Adaptation of the Career Decision Making Profile Measurement Tool for Students in Indonesia - Nandita Tamara Putri; Hery Susanto (Psympathic : Jurnal Ilmiah Psikologi, 2023)
In recent years, there was an increasing interest in the importance of individual differences in career decision making, which reflected the strategy pattern adopted by individuals. Optimal decisions were made by several individual when these strategies were adaptive. Therefore, this study aimed to adapt the measurement tool known as Career Decision Making Profile developed by Gati et al. (2010). To achieve this objective, a quantitative approach was employed, and a convenience sampling technique was used to select a sample of 204 Indonesian students. The results showed that the measurement tool had good internal consistency, with Cronbach's Alpha values ranging from .707 to .762. The Confirmatory Factor Analysis also indicated that the measurement tool model fulfilled the criteria for goodness of fit. Therefore, this tool in the Indonesian language was measured the pattern of career decision making strategies among students.